Tacrolimus/sirolimus vs tacrolimus/methotrexate as GVHD prophylaxis after matched, related donor allogeneic HCT - Cutler, Corey; Logan, Brent; Nakamura, Ryotaro; Johnston, Laura; Choi, Sung; Porter, David; Hogan, William J.; Pasquini, Marcelo; MacMillan, Margaret L.; Hsu, Jack W.; Waller, Edmund K.; Grupp, Stephan; et al. (Blood, 2014)
Grades 2-4 acute graft-versus-host disease (GVHD) occurs in approximately 35% of matched, related donor (MRD) allogeneic hematopoietic cell transplantation (HCT) recipients. We sought to determine if the combination of tacrolimus and sirolimus (Tac/Sir) was more effective than tacrolimus and methotrexate (Tac/Mtx) in preventing acute GVHD and early mortality after allogeneic MRD HCT in a phase 3, multicenter trial. The primary end point of the trial was to compare 114-day grades 2-4 acute GVHD-free survival using an intention-to-treat analysis of 304 randomized subjects. There was no difference in the probability of day 114 grades 2-4 acute GVHD-free survival (67% vs 62%, P = .38). Grades 2-4 GVHD was similar in the Tac/Sir and Tac/Mtx arms (26% vs 34%, P = .48). Neutrophil and platelet engraftment were more rapid in the Tac/Sir arm (14 vs 16 days, P < .001; 16 vs 19 days, P = .03). Oropharyngeal mucositis was less severe in the Tac/Sir arm (peak Oral Mucositis Assessment Scale score 0.70 vs 0.96, P < .001), but otherwise toxicity was similar. Chronic GVHD, relapse-free survival, and overall survival at 2 years were no different between study arms (53% vs 45%, P = .06; 53% vs 54%, P = .77; and 59% vs 63%, P = .36). Based on similar long-term outcomes, more rapid engraftment, and less oropharyngeal mucositis, the combination of Tac/Sir is an acceptable alternative to Tac/Mtx after MRD HCT. This study was funded by the National Heart, Lung, and Blood Institute and the National Cancer Institute; and the trial was registered at www.clinicaltrials.gov as #NCT00406393. •Tac/Sir prophylaxis provides equivalent GVHD-free survival when compared with Tac/Mtx in MRD transplantation.•Tac/Sir is associated with more rapid engraftment and reduced oropharyngeal mucositis after MRD transplantation.